(untitled) (Research, Society and Development, 2025)
Objective: To establish a comprehensive reference on oral biofilm and periodontal health in microgravity, addressing existing knowledge gaps, proposing innovative protocols, and preventive strategies for prolonged space missions. Methods: Narrative review of international literature, integrating clinical data, microgravity experiments, in vitro/in vivo modeling, and computational simulations (Hall-Stoodley et al., 2004; Lewandowski, 2000; Vélez Justiniano et al., 2023). Results: Microgravity alters the composition of the oral microbiome, promotes resistant biofilms, and compromises local immunity (Salido et al., 2025; Koenig & Pierson, 1997). Current protocols partially reduce superficial biofilm but fail to address subgingival biofilm, longitudinal monitoring, and personalized oral hygiene. Innovative strategies include metagenomic sequencing (Srinivasan et al., 2021), tele-dentistry, antimicrobial surfaces, bacteriophage therapies, regenerative scaffolds, and AI for continuous monitoring. Identified gaps have been addressed, suggesting detailed methodologies for future research. Conclusion: Space dentistry emerges as a critical field in light of the challenges that microgravity imposes on the oral microbiome and astronauts’ periodontal health. This review demonstrates that changes in subgingival biofilm, antimicrobial resistance, and local immunosuppression require protocols beyond traditional strategies. Therefore, an integrative model is proposed that employs multi-omics analyses, 3D modeling, bioactive surfaces, personalized immune modulation, and remote monitoring through artificial intelligence and tele-dentistry. By integrating prevention, diagnosis, and advanced therapies into a comprehensive plan, this research scientifically and technologically supports the maintenance of oral health in prolonged space missions, aiding in the development of global and standardized guidelines for space dentistry.